2021
DOI: 10.1002/adhm.202001993
|View full text |Cite
|
Sign up to set email alerts
|

An Immunomodulatory Miniaturized 3D Screening Platform Using Liquefied Capsules

Abstract: A critical determinant of successful clinical outcomes is the host's response to the biomaterial. Therefore, the prediction of the immunomodulatory bioperformance of biomedical devices following implantation is of utmost importance. Herein, liquefied capsules are proposed as immunomodulatory miniaturized 3D platforms for the high-content combinatorial screening of different polymers that could be used generically in scaffolds. Additionally, the confined and liquefied core of capsules affords a cell-mediated 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Previously, we demonstrated that chitosan‐ending capsules as well as the presence of MSCs, favor the balance of the surrounding macrophages toward a more regenerative profile through the up‐regulation of anti‐inflammatory markers and the release of proregenerative cytokines. [ 24 ] Furthermore, the delivery of macrophages has been shown promising to improve fracture healing. Recent in vivo studies have demonstrated that macrophages should be considered as a cell component when constructing biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that chitosan‐ending capsules as well as the presence of MSCs, favor the balance of the surrounding macrophages toward a more regenerative profile through the up‐regulation of anti‐inflammatory markers and the release of proregenerative cytokines. [ 24 ] Furthermore, the delivery of macrophages has been shown promising to improve fracture healing. Recent in vivo studies have demonstrated that macrophages should be considered as a cell component when constructing biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…234 To evaluate the possibility of utilizing microcapsules as an immunomodulatory platform, layer-by-layer technology has been used to produce microcapsules with different outer coatings, which were placed in contact with macrophages. 247 It was found that microcapsules coated in an outer layer of chitosan displayed greater anti-inflammatory properties than capsules presenting other commonly used polyelectrolytes, such as alginate and PLL. Additionally, mesenchymal stem cells such as ASCs have been found to secrete a rich cocktail of chemical factors that can promote tissue regeneration and induce immunomodulation.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…248,249 As such, ASCs were encapsulated within the microcapsules, which were once again placed in contact with a 2D cell bed of macrophages. 247 It was discovered that microcapsules encapsulating ASCs were more successful in the promotion of a pro-healing gene expression profile when compared to empty microcapsules. This immunomodulation-based approach could be used to promote a pro-regenerative immune reaction in the heart, in order to minimize the damage caused in the aftermath of MI.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…For that, in vitro platforms able to predict the immunomodulatory bioperformance of biomedical devices following implantation are of the utmost importance. [149] Despite the great amount of knowledge and progress achieved during the past decades, the clinical translation of TERM strategies still faces a myriad of challenges, including regulatory and economic hurdles, intrinsically correlated with the size of the potential patient market. We believe that the concept herein debated of a "minimalist-engineering" approach, in particular through the use of low material-based bioengineered systems, circumvent the major translational drawbacks found in classical TE strategies.…”
Section: Wrinkled Surface Microparticlesmentioning
confidence: 99%